The Adaption of Infectious Diseases Curriculum of Medical Students to the Future Career Needs of General Practitioners - Parsa Fazeli; Yahya Mohammadi; Zohreh Azarkar; Mohammadreza Raeisoon (Future of Medical Education Journal)
Background: One of the most important missions of universities is social responsibility and meeting the needs of society. This study aimed to evaluate the level of adaption of infectious diseases curriculum of medical students to their future career needs.Method: This cross-sectional study was conducted on all general practitioners working in South Khorasan province who were educated during the period from 2016 to 2020. The inclusion criteria included informed consent of the physicians as well as at least 6 months work experience. The data collection tool was a researcher-made questionnaire with 19 items. The data analysis was conducted by SPSS v. 16 at the significance level of P <0.05.Results: 106 individuals including 50 (47.2%) women and 56 (52.8%) men with a mean age of 28.79 ± 3.10 years were included. Based on the results, the curriculum contents of the infectious diseases department have been effective in improving and developing the knowledge, attitude, and practive of general practitioners. The mean score of adaptation of all of the headings of infectious diseases curriculum of medical students with their future career needs was high and statistically significant (P <0.05). The mean score of the heading "Common Parasitic Diseases" was close to 1.5, and the adaptation of this heading to the future career needs of general practitioners was average and not statistically significant (P=0.107).Conclusion: The curriculum content of the subject under study are at an average level in terms of scientific awareness and theoretical knowledge, as well as applied knowledge in the field of determined needs, and it is necessary to provide conditions to transfer and generalize the necessary skills and abilities and theoretical knowledge in this field to practical and applied situations